5Th EDITION OF THE INTERNATIONAL CONFERENCE ON GLOBAL MANAGEMENT - Peruana de Ciencias Aplicadas, Universidad (2020)
On Wednesday, September 19, the fifth edition of the International Conference on Global Management, entitled "Happiness and Ethics in the Workplace: Two Sides of the Same Coin?" Was held in the "Luis Bustamante" auditorium of the UPC San Isidro campus. ”, Which is organized annually by the Faculty of Business through the  Directorate of Administration and Finance of the UPC, and which was co-organized by the International Finance Corporation (IFC), a member of the World Bank Group, and sponsored by Delta Air Lines.